2000
DOI: 10.1152/ajpendo.2000.279.4.e855
|View full text |Cite
|
Sign up to set email alerts
|

GLUT-3 expression in human skeletal muscle

Abstract: Muscle biopsy homogenates contain GLUT-3 mRNA and protein. Before these studies, it was unclear where GLUT-3 was located in muscle tissue. In situ hybridization using a midmolecule probe demonstrated GLUT-3 within all muscle fibers. Fluorescent-tagged antibody reacting with affinity-purified antibody directed at the carboxy-terminus demonstrated GLUT-3 protein in all fibers. Slow-twitch muscle fibers, identified by NADH-tetrazolium reductase staining, possessed more GLUT-3 protein than fast-twitch fibers. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
8
19
0
Order By: Relevance
“…Consistent with previous studies in human skeletal muscles, we could not detect GLUT3 immunoreactivity in adult skeletal muscle fibres [37], nor could we confirm the fibre-type dependency of GLUT3 [32] when using two different polyclonal antibodies with optimised antibody concentrations. High concentrations of anti-GLUT3 antibodies stained muscle fibres, but at these concentrations liver cells, which do not express GLUT3, also stained.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies in human skeletal muscles, we could not detect GLUT3 immunoreactivity in adult skeletal muscle fibres [37], nor could we confirm the fibre-type dependency of GLUT3 [32] when using two different polyclonal antibodies with optimised antibody concentrations. High concentrations of anti-GLUT3 antibodies stained muscle fibres, but at these concentrations liver cells, which do not express GLUT3, also stained.…”
Section: Discussionsupporting
confidence: 91%
“…Despite GLUT3 being cloned originally from a fetal human skeletal muscle library [21], GLUT3 mRNA is nearly undetectable in adult human muscle [4,18,29,30,36] and only two studies have reported concomitant GLUT3 protein expression [30,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, higher rates of insulin infusion and higher plasma insulin concentrations might increase production of and/or translocation of other glucose transporter isoforms, including GLUT1, which our previous studies did show was responsive to insulin with increased expression and abundance, and GLUT3, which has been found in fetal skeletal muscle (6,14,29,(33)(34)(35)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 91%
“…However, immunofluorescence and immunohistochemical localization of GLUT3 in normal human skeletal muscle demonstrated that GLUT3 protein is distributed throughout the muscle. GLUT3 was shown to be expressed predominantly in slow twitch fibers although at a low level [46] and was mainly localized to the plasma membrane-enriched fractions [47]. The presence of GLUT3 together with GLUT1 and GLUT4 at the plasma membrane could contribute to basal glucose uptake.…”
Section: Glut3mentioning
confidence: 98%